(untitled) (Physical Culture and Sport: Scientific Perspective, 2024)
The article examines the current problems of using the conceptual category «professional sport» in normative documents. It has been proven that a clear consolidation and understanding of the main concepts and terms is the key to the successful implementation of legal norms in any field of legal regulation and their application in practical activities by all subjects; pointed out that the quality of the document itself directly depends on the consistency and logical orderliness of the legal terminology itself, its compliance with national and international standards. The author, referring to the research of scientists, identified the characteristic features of sport as a social institution: the use of a sense of excitement to motivate people to consume sports services; the unstable quality of the sports spectacle as a product and the extremely high loyalty of consumers to it; balance of competition between rivals; the relationship between earnings and the duration of the sports season. The peculiarities of the use of the term «professional sport» are analyzed in order to improve the legal regulation of social relations that are formed between subjects of professional sports activity. Current problems also include cases of equating the definitions of «professional sport» and «high-performance sport». In addition, there is a tendency to intensify a kind of synthesized cooperation between Olympic and professional sports: athletics, fencing, swimming have gone the way of commercialization and professionalization. It was emphasized that despite the differences and different readings, the main common features of the definition were the commercialization of professional sports - making a profit as a result of providing services related to the production and sale of the spectacle, the participation of every component of professional sports: human resources, infrastructure, sports facilities, etc.